Levels and volatility in daily relationship quality: Roles of daily sacrifice motives. (December 2020) - Kayabol, Nazlı Büşra Akçabozan; Gonzalez, Jose-Michael; Gamble, Hilary; Totenhagen, Casey J.; Curran, Melissa A.
Conflicts are inevitable in romantic relationships. Couples sometimes choose the pro-relationship strategy of relational sacrifice to address such conflicts. Previous research established that examining sacrifice motives (i.e., approach and avoidance) is meaningful in understanding relationship quality. Using interdependence theory and 14 days of diaries with 110 heterosexual couples, we extend previous research by testing how sacrifice motives predicted both mean levels and volatility of daily relationship quality (i.e., satisfaction, commitment, intimacy, passion, trust, and love). Specifically, we examined actor and partner reports of sacrifice motives as individuals' average levels (trait; between-person differences) and daily levels of sacrifice motives on a specific day (state; within-person differences) in predicting relationship quality. When predicting mean levels of relationship quality, individuals' own (actor) trait and state approach and avoidance motives predicted most relationship quality variables. Results were less robust for partner effects, especially for partner trait and state approach motives. When predicting volatility (within-person variability across 14 days) in relationship quality, patterns were more robust for both approach and avoidant motives and for both actor and partner effects. For approach sacrifices, and for all six relationship quality variables, individuals' trait approach motives predicted lower volatility, whereas avoidance motives predicted higher volatility. For partner effects, individuals reported lower volatility in satisfaction, intimacy, passion, and trust when their partners were higher in approach motives, whereas they reported higher volatility in satisfaction, commitment, intimacy, and trust when their partners were higher in avoidance motives. We discuss the importance of studying dyads and testing the associations between sacrifice motives and daily relationship quality—both levels and volatility.